What drives profitability in the Romanian ICT sector? - Lucian Belascu; Dan Gabriel Dumitrescu; Alexandra Smedoiu Popoviciu; Alexandra Horobet (Amfiteatru Economic Journal, 2021)
Identifying the major driving factors behind variations in profitability across firms is a question addressed by many researchers, at industry, economic sector, country level, or through regional and international comparisons. Empirical approaches have shown that profitability variation across firms and industries, is the norm, rather the exception. The paper investigates the factors underlying the profitability of Romanian companies in the ICT sector within the company-industry-localization framework, applying the variance components methodology and using aggregate profitability (ROA - Return on assets) as a measure of profitability. The ICT sector in Romania, one of the most dynamic in the last decade and the "winning sector" of the pandemic, operates with different levels of profitability depending on its two main components, Production and Services. At the same time, other disparities resulting from the characteristics of the business - size, personnel costs, productivity - are present. Our results show the high heterogeneity of profitability between firms in the ICT sector, but also the greater importance of the factors intrinsic to the firm compared to that of industry or location factors, which raises the question of whether this sector has incorporated into profitability the tax advantages it enjoys and how sustainable its performance will be once these advantages will diminish.
Keywords: L23; L25; L86; 330; Aggregate profitability (ROA); ICT sector; the firm-industry-localization triad; variance components methodology; Romania